Strategi Badan Pengawas Pemilihan Umum Kabupaten Jombang Dalam Mencegah Pelanggaran Pemilihan Umum 2019 - Mita Wardiyanti; Shobirin Noer; Machwal Huda (Pusat Riset dan Inovasi Nasional, 2023)
Elections are aimed at electing members of representative councils, such as the DPR, DPD and DPRD. After the IV amendment to the 1945 Constitution was implemented in 2002, the President and Vice President Election (Pilpres), which initially used the MPR (People's Consultative Assembly), was agreed to be carried out directly by the people. The 2004 presidential election was the first direct presidential election. Then the second in 2009. The third Presidential election was held directly in 2014. This activity is carried out every five (5) years (Anugerah.Thesis.2017:2018). This research aims to find out and understand what strategies Bawaslu Jombang implemented in an effort to prevent violations in the 2019 Election. The research method used was descriptive qualitative, using informants in this research who were the chairman, secretary and members of Bawaslu Jombang Regency.